An extended abstract of "Metamorphic testing: testing the untestable" - Segura, Sergio; Towey, Dave; Zhou, Zhi Quan; Chen, T.Y. (2019)
This document is an extended abstract of an IEEE Software paper, "Metamorphic Testing: Testing the Untestable," presented as a J1C2 (Journal publication first, Conference presentation following) at the IEEE Computer Society signature conference on Computers, Software and Applications (COMPSAC 2019), hosted by Marquette University, Milwaukee, Wisconsin, USA. © 2019 IEEE.